365 (3NWhI dJMbjb GdKbI HGdfaSs - (3OjajO dhQGfS(B, (3HQjSJhfs ((3GdbGgQI(B:s (3OGQ GdaGQhb(B,s, 2007)
(3GfJ Ydi hTc JZjjQ fXQjc dfaSc JeGeG hGdMUhd Ydi GdeRjO ef GdSYGOI aGSJYO dPdc(B. (3Ef GdKbI HGdfaS ef Cge GdYhGed GdCSGSjI dMjGI SYjOI MjK dG jSJWjY eYXe ef jaJbOhf GdKbI HGdfaS hGMJQGe GdGPGJ EfLGR GdcKjQ aj GdMjGI EPG cfJ JTYQ Cfg jecfc GSJYGOI GMJQGec dfaSc Hbdjd ef GdLgO agPG GdcJGH eKGdj HGdfSHI dc Uee gPG GdcJGH HYfGjI deSGYOJc Ydi GcJSGH GdeRjO ef GdKbI HGdfaS Yf WQjb GSJNOGe HYV GdWQb hGdGSJQGJjLjGJ GdJi CKHJJ UdGMjJgG eY BdGa GdCTNGU aj eNJda HdOGf GdYGde(B. (3jfbSe GdcJGH Edi GKfjf hNeSjf aUdG jMJhi cd efgG Ydi HYV GdeYdheGJ hGdJUhQGJ hGdJeGQjf hGdedMhXGJ GdYedjI hHYV GdfbGW ddJacjQ ajgG hcdeGJ GdJTLjY jcaj Cf JNUU HVY ObGFb dgPG GdcJGH jhejG dJdGMX GdaQb NdGd TgQjf Ch KdGKI hHYO YGe ef GdBf SJfXQ Edi GdhQGA hJfOgT ef GdKbI HGdfaS GdJj GcJSHJgG NdGd gPG GdhbJ(B. s
Keywords: (3GdJfejI GdHTQjIs; (3GdKbI HGdfaSs